Decree No. 214 of the Year 2025 = قرار رقم 214 لسنة 2025 - Ministry of Labour; وزارة العمل (The Middle East Library For Economic, 2025)
Article-1 Definition of Employment Contract: Employment contract is the contract by virtue of which a worker promises to work for an employer and under his control or supervision in return for a wage. Article-2 Drawing up and Lodging the Contract: The employer shall draw up the employment contract in written form in Arabic language. It shall be made in four copies, one copy shall be maintained thereby in the worker’s file, another copy shall be delivered to the worker, a third copy shall be lodged with the insurance office and a fourth copy shall be lodged with the competent administrative entity